DIRECT MANUFACTURING OF METAL PARTS USING LOM-TECHNOLOGY - N. K. Tolochko; A. A. Andrushevich; P. S. Chugaev; T. A. Bogdanobich (Литьë и металлургия)
A brief review of the main types of additive technologies providing direct manufacturing of metal parts was carried out. Peculiarities of direct manufacturing of metal parts using LOM-technology (laminated object manufacturing) are compared with other additive technologies. Different methods of juncture stacked sheet metals during fabrication of LOM-parts, including methods of mechanical, adhesive, welded and soldered juncture were analyzed. The advantages and disadvantages of each of these methods were considered. The possibilities of juncture sheet stacked metals by welding and soldering were demonstrated experimentally.